Deposit Protection Arrangements : A Survey - Kyei, Alexander (IMF Working Papers; Working Paper ;, 1995)
This paper is a survey of deposit protection arrangements and it compares the key elements of deposit protection schemes around the world. There are more implicit arrangements that guarantee deposits than explicit ones, but there has been a growing tendency since the 1980s for countries to adopt explicit ones largely in response to emerging problems with their financial systems.